1994
DOI: 10.1007/bf00150349
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient accumulation and translocation in maturing wheat plants grown on waterlogged soil

Abstract: Wheat plants (Triticum aestivum L., cv. Arina) growing in large pots (perforated at the bottom for controls, intact for flooding) were embedded in the field in spring. Waterlogging was initiated at anthesis and was maintained throughout the maturation period. Grain yield as well as potassium, phosphorus and magnesium contents in the shoot were decreased on flooded soil, while manganese and iron contents increased considerably. Total calcium and zinc contents per shoot remained comparable to those in controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 24 publications
5
29
1
2
Order By: Relevance
“…Result of this study were in agreement with the finding of Stieger and Feller,[21] reported higher Fe and Mn contents can be detected in wheat shoots (Figure 1). …”
Section: Leadsupporting
confidence: 93%
“…Result of this study were in agreement with the finding of Stieger and Feller,[21] reported higher Fe and Mn contents can be detected in wheat shoots (Figure 1). …”
Section: Leadsupporting
confidence: 93%
“…Fe and Mn are reduced in waterlogged soil to the well water-soluble Fe ++ and Mn ++ ions increasing for these two elements the concentration in the soil solution [70]. As a consequence, higher Fe and Mn contents can be detected in wheat shoots under such conditions [70].…”
Section: Redistribution Via the Phloemmentioning
confidence: 99%
“…If there would be no further redistribution, the heavy metals would accumulate primarily in photosynthetically active (transpiring) leaves. Such an accumulation with no or only a minor redistribution was observed for the micronutrient Mn as well as for the macronutrient Ca and to a minor extent for Fe (Figures 2 and 3) [2,[67][68][69][70]. Although the xylem vessels are dead, membranes of living cells around the vessels allow a selective removal of ions from the xylem sap [68,69].…”
Section: Transport With the Transpiration Stream In The Xylemmentioning
confidence: 99%
See 2 more Smart Citations